PENILAIAN KINERJA DALAM UPAYA PENINGKATAN PELAYANAN PUBLIK - Sugiyarti, Sri Riris (Transformasi, 2011)
Abstract   One of the important issues that develop on the sidelines of a revolving future issue of democratization reforms is a matter of the ability of local governments in providing services to people in the region. Issues - issues concerning the need to increase the ability of the organizers of the local government, both  personal and organizational capabilities, such as in a programming problem, preparation of work plans an integral part of efforts to improve government management to good governance. Public Service is any service activity conducted by the organizers of the Public Service as an effort to fulfill the needs of the service recipient or the implementing provisions of the legislation. The nature of public services is the provision of Quality Service with improved quality of service to the community which embodies the Government Apparatus obligations as Abdi society. Government through the bureaucracy in carrying out public services to the community should also be adhered to the principle - the principle of service publk namely: Transparency, Accountability, Conditional, Participatory, Equality & balance of rights and obligations. Local governments through public service agencies must be able to perform public service professionals. Development Strategy by the Local Government Public Service must be performed continuously to meet the needs and increase public satisfaction through 7 Simple Strategic for Success. Local governments in carrying out public service should always make corrections on - constantly including the renewal of Organizational Performance of public services based on changes in organizational culture, organizational structure, resource development and leadership bureaucrats who have the vision and mission development, increase the capacity of local government policy in public service .   Key word :  Development, Public service, Government